2010
DOI: 10.1007/s10140-010-0860-4
|View full text |Cite
|
Sign up to set email alerts
|

CT and MR imaging of primary cerebrovascular complications in pediatric head trauma

Abstract: The incidence of severe traumatic head injury in children has constantly increased over the last years. Diagnostic imaging has become an unrenounceable tool for the documentation and follow-up of intracranial lesions. The use of magnetic resonance imaging (MRI) in the early posttraumatic phase has led to a more thorough understanding of intracranial injuries. We retrospectively analyzed the cranial computed tomography (CCT) and magnetic resonance (MR)-studies of patients with traumatic head injuries for primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Complications of severe head trauma-such as sutural diastasis and/or skull fracture with mechanical compression or disruption of the venous sinus, shock, cerebral edema, poor cerebral perfusion, and coagulopathies-are also associated with the development IVT. 8 Our hypothesis is that if extra-axial hemorrhage is the result of IVT, then children with IVT from nontraumatic causes would be at risk to develop subdural collections. Our review of the pediatric literature revealed no previous study that systematically addressed the association of nontraumatic pediatric IVT with convexity SDH in children beyond the neonatal period.…”
mentioning
confidence: 99%
“…Complications of severe head trauma-such as sutural diastasis and/or skull fracture with mechanical compression or disruption of the venous sinus, shock, cerebral edema, poor cerebral perfusion, and coagulopathies-are also associated with the development IVT. 8 Our hypothesis is that if extra-axial hemorrhage is the result of IVT, then children with IVT from nontraumatic causes would be at risk to develop subdural collections. Our review of the pediatric literature revealed no previous study that systematically addressed the association of nontraumatic pediatric IVT with convexity SDH in children beyond the neonatal period.…”
mentioning
confidence: 99%
“…Outside of the perinatal period, predisposing factors include dehydration, an underlying malignancy or chemotherapy (primarily with asparaginase), iron deficiency anemia, infection or sepsis, or thrombophilia from, for example, protein C or protein S deficiency, MTHFR gene mutations or oral contraceptive use [4,31]. Trauma is an important precipitating factor of cortical sinus and venous thrombosis and can be caused by direct trauma (laceration) to a sinus or vein; sinus compression (leading to slowing or cessation of flow) by a depressed skull fracture, adjacent hematoma or cerebral edema or swelling [33]; and intramural hemorrhage caused by rupture of small sinusoids, injury to the endothelial lining, or extension of thrombus from injured emissary veins [34]. Traumatic dural venous sinus thrombosis can be found in 40% of patients with blunt head trauma who had skull fracture extending to a dural venous sinus or jugular bulb [35].…”
Section: Primary Versus Secondary Thrombosismentioning
confidence: 97%
“…This information is used to determine what neurosurgical interventions are necessary and to provide prognostic information about long-term developmental outcomes (Beauchamp et al, 2011; Suskauer & Huisman, 2009). Cranial CT scans are useful in identifying large hematomas, midline shift, skull fractures, excess CSF accumulation in the ventricles, cerebral edema, and brain herniation (Steinborn et al, 2010; Suskauer & Huisman, 2009). The results of the initial CT scans are used to determine if emergent neurosurgical interventions (e.g., decompression craniotomy) are needed (Suskauer & Huisman, 2009).…”
Section: Assessing and Monitoring Children With Severe Tbimentioning
confidence: 99%